Three-dimensional elastic properties of masonry by mechanics of structure gene. (15th May 2020) - Almeida, Francisco P.A.; Lourenço, Paulo B.
Highlights: MSG is applied for the first time to the homogenization of masonry. The results agree with numerical or theoretical methods, including a 3D FEA. MSG considerably reduces the computational cost. 3D properties are obtained from the solution of 2D problems. Absence of necessity of applying boundary conditions. Abstract: Masonry is a composite material formed by units and joints, highly anisotropic and difficult to characterize. This paper presents the application of Mechanics of Structure Gene (MSG) to the homogenization of masonry. Since it is a semi-analytical technique, MSG considerably reduces the computational cost and maintains the same precision of three-dimensional (3D) analyses, for example, by the Finite Element Method. Other interesting features are the possibility of obtaining 3D properties from the solution of 1D or 2D problems and the absence of necessity of applying boundary conditions. In the analyzed examples, the 3D elastic constants of the masonry, considered as an anisotropic material, are calculated from Young's modulus and Poisson's ratio of the blocks (or units) and the mortar joints, considered as isotropic. The results obtained are compared with numerical or theoretical methods by different authors, including a 3D finite element analysis, and present agreement, even for large ratios between Young's moduli of blocks and mortar. Thus, the results presented in the paper show that the MSG method can be successfully applied in the homogenization of masonry and presents advantages over other methods for the same purpose.